2006
DOI: 10.1111/j.1442-1984.2006.00159.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in Fagus multinervis Nakai (Fagaceae), a beech species endemic to Ullung Island, South Korea

Abstract: The genetic variation of Fagus multinervis Nakai (Fagaceae), which is endemic to Ullung Island, South Korea, was investigated using allozyme polymorphisms as a genetic marker. A total of 1074 individuals collected from five populations were analyzed and the levels of genetic diversity were compared to those of Fagus japonica and Fagus crenata distributed in Japan. The percentages of polymorphic loci and the number of alleles per locus of F. multinervis were similar to those of the other beech species and to ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Accordingly, the life span of F. crenata is approximately 150-300 yr (Hagiwara 1988;Kitamura et al 2007), while that of F. japonica cannot be accurately estimated because of sprouting but could be more than 1000 yr (Hara 1996). The long life span of F. japonica may retard the loss of genotypes through death and allow populations to accumulate genetic diversity, as indicated by previous allozyme studies of F. japonica (Kitamura et al 1992) and Fagus multinervis Nakai (another sprouting, multistemmed beech) as well as F. japonica (Ohkawa et al 2006). This inference is supported by a review of allozyme-based studies indicating that within-population diversity is generally significantly higher for woody plant species that regenerate both sexually and asexually (and thus possibly have a long life span) than for those that regenerate solely sexually (Hamrick et al 1992).…”
Section: No Geographic Trends In Genetic Diversity Within F Japonicamentioning
confidence: 86%
“…Accordingly, the life span of F. crenata is approximately 150-300 yr (Hagiwara 1988;Kitamura et al 2007), while that of F. japonica cannot be accurately estimated because of sprouting but could be more than 1000 yr (Hara 1996). The long life span of F. japonica may retard the loss of genotypes through death and allow populations to accumulate genetic diversity, as indicated by previous allozyme studies of F. japonica (Kitamura et al 1992) and Fagus multinervis Nakai (another sprouting, multistemmed beech) as well as F. japonica (Ohkawa et al 2006). This inference is supported by a review of allozyme-based studies indicating that within-population diversity is generally significantly higher for woody plant species that regenerate both sexually and asexually (and thus possibly have a long life span) than for those that regenerate solely sexually (Hamrick et al 1992).…”
Section: No Geographic Trends In Genetic Diversity Within F Japonicamentioning
confidence: 86%
“…A strong isolation of populations at different altitudes may be observed because of mountain barriers and drastic differences in phenology between lower and higher elevations, which restricts the gene flow and leads to genetic differentiation (Runions and Geber 2000;Arnaud-Haond et al 2006). As a result, patterns of genetic variation along altitudinal gradients are complex and varied (Ohkawa et al 2006;Jump et al 2006;Kandedmir et al 2004;Byars et al 2009). The variability of specific species on mountains is significant when assessing the distribution, evolution and adaptive ability, and providing indicators of conservation strategies of alpine plants (Yan et al 2009;Jump et al 2006;Truong et al 2007).…”
Section: Introductionmentioning
confidence: 95%
“…1998; Takenaka et al . 2002) and Korean beech ( Fagus multinervis ) populations (Ohkawa et al . 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In a series of studies, we have examined the demographic genetic substructuring of American beech (Fagus grandifolia Ehrh.) (Kitamura et al , 2000(Kitamura et al , 2003), Siebold's beech (Fagus crenata) (Kawano & Kitamura 1997;Kitamura et al 1997a,b;Ohkawa et al 1998;Takenaka et al 2002) and Korean beech (Fagus multinervis) populations (Ohkawa et al 2006). These studies have demonstrated clear patterns of genetic differentiation in relation to demographic genetic substructuring within the populations examined (cf.…”
Section: Introductionmentioning
confidence: 99%